Anatomy of regional price differentials: Evidence from micro price data - Sebastian Weinand; Ludwig von Auer (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2019)
Our paper uses micro price data collected from Germany's Consumer Price Index to compile a highly disaggregated regional price index for the 402 counties and cities of Germany. We introduce a multi-stage version of the weighted Country-Product- Dummy method. The unique quality of our price data allows us to depart from previous spatial price comparisons and to compare only exactly identical products. We find that the price levels are spatially autocorrelated and largely driven by the cost of housing. The price level in the most expensive region is about 27 percent higher than in the cheapest region.
Keywords: C21; C43; E31; O18; R10; 330; spatial price comparison; regional price index; PPP; CPD-method; hedonic regression; consumer price data